Case reportJuvenile psoriatic arthritis – a case report - Rutkowska-Sak, Lidia; Rell-Bakalarska, Maria; Lisowska, Barbara; Słowińska, Iwona (Reumatologia/Rheumatology, 2006)
An 11-year case history of a patient aged 24 with spondylitis intractu juvenile psoriatic arthritis. The clinical picture, diagnostic problem and disease out come are described.